Lysophosphatidic Acid and Several Neurotransmitters Converge on Rho-Kinase 2 Signaling to Manage Motoneuron Excitability - García-Morales, Victoria; Gento-Caro, Ángela; Portillo, Federico; Montero, Fernando; González-Forero, David; Moreno-López, Bernardo (Frontiers in Molecular Neuroscience, 2021)
Intrinsic membrane excitability (IME) sets up neuronal responsiveness to synaptic drive. Several neurotransmitters and neuromodulators, acting through G-protein-coupled receptors (GPCRs), fine-tune motoneuron (MN) IME by modulating background K+ channels TASK1. However, intracellular partners linking GPCRs to TASK1 modulation are not yet well-known. We hypothesized that isoform 2 of rho-kinase (ROCK2), acting as downstream GPCRs, mediates adjustment of MN IME via TASK1. Electrophysiological recordings were performed in hypoglossal MNs (HMNs) obtained from adult and neonatal rats, neonatal knockout mice for TASK1 (task1–/–) and TASK3 (task3–/–, the another highly expressed TASK subunit in MNs), and primary cultures of embryonic spinal cord MNs (SMNs). Small-interfering RNA (siRNA) technology was also used to knockdown either ROCK1 or ROCK2. Furthermore, ROCK activity assays were performed to evaluate the ability of various physiological GPCR ligands to stimulate ROCK. Microiontophoretically applied H1152, a ROCK inhibitor, and siRNA-induced ROCK2 knockdown both depressed AMPAergic, inspiratory-related discharge activity of adult HMNs in vivo, which mainly express the ROCK2 isoform. In brainstem slices, intracellular constitutively active ROCK2 (aROCK2) led to H1152-sensitive HMN hyper-excitability. The aROCK2 inhibited pH-sensitive and TASK1-mediated currents in SMNs. Conclusively, aROCK2 increased IME in task3–/–, but not in task1–/– HMNs. MN IME was also augmented by the physiological neuromodulator lysophosphatidic acid (LPA) through a mechanism entailing Gαi/o-protein stimulation, ROCK2, but not ROCK1, activity and TASK1 inhibition. Finally, two neurotransmitters, TRH, and 5-HT, which are both known to increase MN IME by TASK1 inhibition, stimulated ROCK2, and depressed background resting currents via Gαq/ROCK2 signaling. These outcomes suggest that LPA and several neurotransmitters impact MN IME via Gαi/o/Gαq-protein-coupled receptors, downstream ROCK2 activation, and subsequent inhibition of TASK1 channels.